Laboratory assessment of the quality of adult and neonatal red cell concentrates manufactured from whole blood, exchange transfusion or intrauterine transfusion red cell units. Issue 5 (17th May 2018) - Meli, A.; New, H.; McAndrew, M.; Wiltshire, M.; Cardigan, R.
Abstract : Background: We evaluated the quality of red cell components in additive solution over 42 days of storage when re‐manufactured from neonatal exchange transfusion (ExTx) or intrauterine transfusion (IUT) units on day 7 for issue to adults, neonates or infants. Materials and methods: Red cell concentrates (RCC) manufactured from WB were compared to RCC re‐manufactured from ExTx or IUT on day 7, and red cell splits (RCS) manufactured from WB were compared to RCS re‐manufactured from ExTx or IUT on day 7. All components were stored at 2–6°C and tested throughout storage until day 42 for in vitro parameters of red cell quality. One RCS manufactured from each of WB, ExTx or IUT, was irradiated on day 14 and tested on day 28 along with a non‐irradiated RCS from the same unit. Results: All the re‐manufactured arms had no worse haemolysis, red cell microvesicle (RCMV) release or ATP over storage compared to controls. All arms complied with the 0·8% haemolysis UK specification, except for re‐manufactured RCS from the IUT arm irradiated on day 14 and tested on day 28. Re‐manufactured units had significantly decreased potassium levels compared to control over storage ( P < 0·001 all). Conclusion: RCC or RCS re‐manufactured from ExTx or IUT units on day 7 are suitable for transfusion up to the standard day 35 of storage. Re‐manufactured RCS from ExTx units (but not IUT), may be irradiated up to day 14 and stored for 14 days post‐irradiation.